Does CSR performance improve corporate immunity to the COVID-19 pandemic? Evidence from China's stock market - Tian, Jing; Wang, Xiuxiu; Wei, Yanqiu (Frontiers in Public Health, 2022)
This paper studies the role of corporate social responsibility (CSR) performance on corporate financial performance during the Covid-19 by examining a sample of Chinese listed firms. Based on the PSM-DID methodology, we find that the pandemic-induced decline in stock returns is stronger with more CSR engagement. The results remain robust even after the dynamic effect test and placebo test. It means CSR performance does not improve Chinese corporate immunity to the pandemic. This inadequate response of CSR could be due to the "relatively few good things effect". Furthermore, our study indicates that increasing awareness of responsible investment and improving the quality of CSR disclosure could facilitate CSR engagement in China.